IDENTITY TEST OF VOLUMETRIC MODELS FOR Pinusoocarpa AND Pinuscaribaea VAR. Hondurensis IN MIXED STAND IN SOUTHWEST BAHIA - ARAGÃO, Mariana de Aquino; BARRETO-GARCIA, Patrícia Anjos Bittencourt; LEITE, Marcos Vinícius Santana; CARVALHO, Flávia Ferreira de; VIRGENS, Aline Pereira das (Brazilian Journal of Biometrics, 2016)
Wood volume measuring brings vital information about the productive potential of a forest. Normally, volume information is obtained with the use of volumetric equations from regression models, adjusted from data obtained by precise timber measurements. However, the equations are commonly generated for specific conditions, such as for certain species, age, location, etc. Therefore, this study aimed to adjust individual volumetric models for the species of Pinus oocarpa and Pinus caribaea and assess the possibility of adjusting a common equation to estimate the volume of both species. The study was conducted on a 13 year old population. Field measurements for precise tree volume were taken for 80 individuals, adjusting volumetric models of simple and double entry. The best model was selected according to the coefficient of determination (R2%), standard error of the estimate (Sxy %) and a visual analysis of the residual distribution. The identity of these models was tested with dummy variables, through covariance analysis. The Schumacher and Hall Log model provided the best results. The identity test indicated that it is not possible to use one equation to, accurately, estimate the volume of both species.